2016
DOI: 10.1186/s40246-016-0094-y
|View full text |Cite
|
Sign up to set email alerts
|

Head-and-neck squamous cell carcinoma risk in smokers: no association detected between phenotype and AHR, CYP1A1, CYP1A2, or CYP1B1 genotype

Abstract: BackgroundHead-and-neck squamous cell carcinoma (HNSCC) differs between smokers and nonsmokers in etiology and clinical presentation. Because of demonstrated unequivocal involvement in smoking-induced cancer in laboratory animals, four candidate genes––AHR, CYP1A1, CYP1A2, and CYP1B1––were selected for a clinical genotype-phenotype association study of HNSCC risk in smokers. Thirty-six single-nucleotide variants (mostly tag-SNPs) within and near these four genes [16 (AHR), 4 (CYP1A1), 4 (CYP1A2), and 12 (CYP1B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The previous studies found that the combination (multiple-variant haplotype) of multiple AhR polymorphisms contributed to the susceptibility of lung cancer [ 13 , 24 ]. Jorge-Nebert et al constructed multiple-variant haplotypes of AhR gene to investigate the association of theses haplotypes with head-and-neck squamous cell carcinoma, but no AhR haplotypes displayed statistically significant correlation with the risk of that cancer [ 36 ]. Haplotypic analysis which has bigger statistical power than single polymorphism analysis was carried out by some original studies, but it was impossible to perform the corresponding meta-analysis of AhR haplotypes attributing to inadequate haplotype data.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies found that the combination (multiple-variant haplotype) of multiple AhR polymorphisms contributed to the susceptibility of lung cancer [ 13 , 24 ]. Jorge-Nebert et al constructed multiple-variant haplotypes of AhR gene to investigate the association of theses haplotypes with head-and-neck squamous cell carcinoma, but no AhR haplotypes displayed statistically significant correlation with the risk of that cancer [ 36 ]. Haplotypic analysis which has bigger statistical power than single polymorphism analysis was carried out by some original studies, but it was impossible to perform the corresponding meta-analysis of AhR haplotypes attributing to inadequate haplotype data.…”
Section: Discussionmentioning
confidence: 99%
“…The substrate-inducible CYP1A1 and CYP1A2 are responsible for xenobiotic metabolism, such as polycyclic aromatic hydrocarbon metabolism [36][37][38][39][40]. In this group, charred food and cigarette smoke catalyze N-oxidation of carcinogenic aromatic and heterocyclic amines [41][42][43]. The enzymes are selective for planar molecules, which are carcinogens, as substrates.…”
mentioning
confidence: 99%